Morphology Controlled Synthesis of α-GaO(OH) Nanoparticles: Thermal Conversion to Ga2O3 and Photocatalytic Properties - Ayse Dulda (Advances in Materials Science and Engineering)
Morphology controlled α-GaO(OH) particles have been synthesized via precipitation method which allows the tuning of relative growth rates of crystal facets. The effects of alkali addition rate and the type of alkali on the growth rates of the crystal facets during hydrolysis were also investigated. XRD and TG analysis confirmed that there was a phase transition from GaO(OH) to Ga2O3 when precursor sample was calcined to 750°C. The single phase α-Ga2O3 was obtained after thermal treatment of NaOH precipitated precursor, while β-Ga2O3 was formed when the urea or NH4OH precipitated precursor was calcinated. Furthermore, the thermal, spectral, and photocatalytic properties connected to the crystal structure and morphology were discussed.